1988
DOI: 10.1037/0021-843x.97.4.429
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the psychological and hormonal factors in women with and without premenstrual syndrome.

Abstract: Women with premenstrual syndrome (PMS; n = 14) were compared with women without premenstrual syndrome (n = 14). The diagnosis was based on the volunteers' responses to the Premenstrual Assessment Form, their medical history, a physical examination, and the Utah PMS Calendar. After assignment to the non-PMS or PMS group, each subject was studied for one menstrual cycle and was evaluated, once during the follicular phase and twice during the luteal phase. On each of these occasions, circulating concentrations of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
0

Year Published

1989
1989
2002
2002

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 16 publications
1
12
0
Order By: Relevance
“…McFarlane and Williams (1990) list no less than 19 examples of proposed medical etiologies. For example, some studies have found that women who suffer from PMS have chronically lower levels of progesterone (e.g., Trunell, Turner, & Keye, 1988), an observation that is consistent with the rapid fall in levels during the premenstrual week. However, their role in PMS, if any, is certainly unclear (Mortola, 1998).…”
mentioning
confidence: 76%
“…McFarlane and Williams (1990) list no less than 19 examples of proposed medical etiologies. For example, some studies have found that women who suffer from PMS have chronically lower levels of progesterone (e.g., Trunell, Turner, & Keye, 1988), an observation that is consistent with the rapid fall in levels during the premenstrual week. However, their role in PMS, if any, is certainly unclear (Mortola, 1998).…”
mentioning
confidence: 76%
“…That psychologic stress can be deleterious to one's physical and mental status because of the psychosomatic or mind-body relationship is a well-documented concept. The manner in which people attempt to understand or explain the causes of a stressful or adverse life eventparticularly the habit of making pessimistic explanationscan significantly undermine their psychologic and physiologic functioning (Peterson & Seligman, 1987; Seligman, 1987; Trunnell, 1986; Weary, Stanley, & Harvey, 1989) or adversely affect the course of a disease (Levenson & Bemis, 1991). Obtaining patient compliance during treatment is a major issue in managing virtually all physical and psychologic problems.…”
mentioning
confidence: 99%
“…c*ql 987). a necessary but not sufficient cause for development of PMS &eye & Trunnell, 1986). Thusitispossible thatelimination of premenstrual syndrome in western culture may be found only in prevention of its psychological and social pathology.…”
Section: Discussionmentioning
confidence: 99%